(untitled) (Palíndromo, 2025)
This research is the result of a research stay funded by the University of Castilla-La Mancha, conducted by a Spanish teacher in collaboration with a Portuguese teacher at the University of Minho. It proposes two consecutive objectives: first, to promote reflection among professionals working in the pedagogical services of contemporary art exhibition spaces on the activities they develop with schools in the area of influence of the University of Minho, Portugal. Secondly, the objective of developing transformative aspects of these realities, based on the observations of the professional who carry them out and trough collaboration with the university from the area of art education in initial teacher training. As a methodology Community-Based Participant Research (CBPR), which develops collaborative research that involves the participants themselves in a critical analysis of their environment, within the scope of the project “Arts Education: School and Museum”, which analyzes the perception that pedagogical or cultural mediation services have of their activities with educational centers. The results allow us to adjust strategies in the initial training of educators and teachers, seeking to reflect positive aspects or strengths along with aspects that need improvement or weaknesses in these environments. In conclusion, we propose keys to analyzing this reality and establish avenues for collaboration between schools and the university.